2015
DOI: 10.1155/2015/848595
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Defense in Endometriosis and Its Malignant Transformation

Abstract: The aim of this study was to investigate the role of redox status in endometriosis and its malignant transformation. A search was conducted between 1990 and 2014 through the English language literature (online MEDLINE PubMed database) using the keywords endometriosis combined with malignant transformation, oxidative stress, and antioxidant defense. In benign endometriosis, autoxidation and Fenton reaction of hemoglobin from the ferrous Fe2+ (oxyhemoglobin) state to the ferric Fe3+ (methemoglobin) state lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 45 publications
6
95
1
Order By: Relevance
“…Furthermore, we hypothesize that other absorbing species are likely to be present in cyst fluid, including hemichromes, and possibly ferrylhemoglobin, sulfhemoglobin or deoxyhemoglobin (deoxyHb), although the levels of each of these species may be relatively low. Also, the absorbance of the samples at each wavelength is the result of the sum of the products of the extinction coefficients of each of the species present in the sample, multiplied by the concentration of those species (8). Therefore, the ratio of the absorption measured at 620 nm divided by that measured at 580 nm does not accurately report the metHb/(oxyHb+metHb) ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we hypothesize that other absorbing species are likely to be present in cyst fluid, including hemichromes, and possibly ferrylhemoglobin, sulfhemoglobin or deoxyhemoglobin (deoxyHb), although the levels of each of these species may be relatively low. Also, the absorbance of the samples at each wavelength is the result of the sum of the products of the extinction coefficients of each of the species present in the sample, multiplied by the concentration of those species (8). Therefore, the ratio of the absorption measured at 620 nm divided by that measured at 580 nm does not accurately report the metHb/(oxyHb+metHb) ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and particularly oxidative stress, which is secondary to the influx of erythrocytes and subsequent hemolysis that occurs during retrograde menstruation and inner hemorrhage in endometriotic lesions, may be one of the causative factors in carcinogenesis (4). Hemoglobin (Hb), heme and iron may have a significant impact on oxidative stress in the development of endometriosis and malignant transformation (8). Therefore, metallobiology studies on Hb-mediated oxidative damage and antioxidant response are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low‐to‐moderate ROS level is indispensable to normal cellular proliferation, differentiation and survival 3. The net emission of ROS depends upon the balance between free radical production (pro‐oxidative process) and its elimination by antioxidants (antioxidant defense process) 4. Peroxiredoxins (PRDXs), a family of this kind of antioxidants, are classified on the basis of having either one (1‐Cys) or two (2‐Cys) conserved cysteine residues 5.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in research on the pathogenesis of EAOC is based on key developments in two areas: i) New mechanistic concepts regarding the pathogenesis of EAOC revealed a key role of hemoglobin (Hb), heme and iron-induced oxidative stress in the OE cystic fluid, wherein an imbalance between the overproduction of iron-induced oxidative stress and defense mechanisms could trigger DNA damage and carcinogenesis; and ii) the establishment of novel approaches to identify stress biomarkers, such as Hb and iron, for the prediction of malignant transformation (2,6,7). A recent ex vivo study revealed that electronic absorption spectroscopy using visible light at 580 and 620 nm provides a measure of Hb species in endometriotic cystic fluid by monitoring the relative concentrations of oxyhemoglobin and methemoglobin, respectively (8).…”
Section: Introductionmentioning
confidence: 99%